Søren Kierkegaards boggaver til den skandinaviske forening i Rom - Bruun, Niels W.; Jensen, Finn Gredal (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2014)
The article surveys the background of Søren Kierkegaard’s donations of his works to the library of the Scandinavian Society in Rome; it presents and discusses the relevant correspondence in 1847 between Professor H.N. Clausen and Kierkegaard, and on the basis of practical investigations in Rome it suggests which ﬁrst editions may have been donated.